HUBUNGAN KECEMASAN TERHADAP KECENDERUNGAN NOMOPHOBIA PADA MAHASISWA D3 KEBIDANAN DI UNIVERSITAS MEGAREZKY MAKASSAR TAHUN 2024 - Ibrahim, Sitti Hasrah; Irmadani, Andi Syarifah; Rikhaniarti, Tri (JURNAL KESEHATAN DELIMA PELAMONIA, 2025)
The existence of smartphones as a tool for communicating with other people andas a tool for searching for information in the current technological era reallyhelps with activities in everyday life. However, without realizing it, high intensityuse of smartphones can cause various negative impacts for users. The aim of thisresearch is to find out whether there is a relationship between anxiety andnomophobic tendencies in D3 Midwifery Students at Megarezky University in2024. This research is quantitative research, the research design used is QuasyExperimental with a one group pretest-posttest design. The sample used was 36D3 Midwifery Students at Megarezky University. The results of this study showedthat 9 respondents (25.0%) had mild anxiety, while 15 respondents had moderateanxiety (11.0%) and 16 respondents (44.0%) had severe anxiety and 16respondents (44.0%) had moderate anxiety. There were 8 respondents (22.0%)with low Nomophobia tendencies and 12 respondents (33.0%) with moderateNomophobia tendencies, while 16 respondents (44.0%) had severe Nomophobiatendencies. The results of statistical analysis using the Chi Square test with a 2x3table, and the significance level (α=0.05) obtained a value of ρ=0.001. If the valueρ<a, this indicates that (Ha) is accepted and (Ho) isrejected, meaning that thereis a relationship between Anxiety and Nomophobic Tendencies in D3 MidwiferyStudents at Megarezky University in 2024. This research is expected to be able tocontrol the use of smartphones wisely by doing a lot positive things such aslearning and reducing feelings of anxiety so that the intensity of usingsmartphones is reduced.Keywords: Anxiety, Nomophobia, D3 Midwifery Students.